Development of portfolio management tools in crop breeding programs: a case study of cassava in sub-Saharan Africa - Egesi, C.; Mbanjo, E.; Kawuki, R.; Teeken, B.; Rabbi, I. Y.; Prempeh, R. N.; Jiwuba, L.; Njoku, D.; Kulembeka, H.; Gwandu, F.; Woyengo, V. W.; Parkes, E.; et al. (Frontiers Media, 2024)
The response to the diverse needs along the cassava value chain, the urge to increase genetic gain, and the need for rapid varietal turnover will necessitate not only technological innovations but also transformation of public breeding programs in sub-Saharan Africa (SSA). We developed guiding, flexible and adaptative tools for portfolio management of cassava breeding. The cassava breeding and product development pipeline process was mapped to illustrate activities of each stage, as well as to clarify key decision points. Stakeholders involved at all stages of breeding were identified. This allowed for identification of gaps and new crucial functions. To clarify accountability and reduce complexity in the decision-making at key decision points, the roles were mapped against decision-rights at each stage-gate. Cassava crop calendars for the different regions in SSA were developed to facilitate better planning. A product advancement template was developed to guide product advancement. The tools that have been developed and stage-gate mapping, will support regional efforts to establish more structured, transparent, participatory, efficient, inclusive, and demand-driven cassava breeding in the region. These approaches could be customized to other commodities.